Banking union with a sovereign virus: The self-serving treatment of sovereign debt - Daniel Gros (Intereconomics, 2013)
Despite the experience of the ongoing sovereign debt crisis, European banks continue to hold large amounts of bonds from their home governments. This ties the fates of the sovereign and the banks together, leading to the disruptive self-reinforcing feedback loops that brought the euro area to the brink of collapse. This article addresses how banks can be weaned off of their massive investments in their home government's bonds.
Keywords: 330